Morpho-Physiological Response of Indonesian Rice (Oryza sativa L.) Under Combination Heat and Drought Stress - Hartatik, Sri; Wardani, Dewi Kusuma; Choirunnisa, Eviyanti; Avivi, Sholeh; Puspito, Agung Nugroho; Kim, Kyung Min; Ubaidillah, Mohammad (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
Heat stress and drought are combination of stresses that have the potential to occur simultaneously in extreme temperature changes. Rice is the main food crop in Indonesia and includes plants that are sensitive to stress. Indonesian local rice is believed to have high adaptability to Indonesian's geographical conditions, however there is lack of updated data to explain this information. This study attempts to determine the level of adaptability or resistance of Indonesian local rice to a combination of heat stress and drought. The results showed that the 24 Indonesian local rice accessions were divided into 3 resistance classes. The high resistance class is Sintha, the resistance classes are Gajah Mungkur, Kalimutu, Kapuas, Sukamandi, Seratus Malam, Cabacu, Bengawan Solo and Cisokan, as well as the medium resistance classes Jatiluhur, Batang Ombilin, Mahakam, Nona Bokra, Pucuk, Bengawan, Rojolele, IR64, Barumun, Cisadane, Memberamo, Cibodas, Gilirang, Fatmawati and Ciherang.